Analisis Gaya Kepemimpinan Yang Efektif Terhadap Kinerja Karyawan Generasi Z (Gen Z) Di Rumah Sakit Umum Aulia Berdasarkan Key Performance Indicator (KPI) Tahun 2023–2024: Analysis of Effective Leadership Styles on the Performance of Generation Z (Gen-Z) Employees at Aulia General Hospital Based on the Key Performance Index (KPI) in 2023–2024 - Alfira Pangestika; Tri Budi Wahyuni Rahardjo; Haidar Istiqlal; Bachtiar Fanani (Journal of Nursing Education and Practice, 2025)
Introduction: Leadership styles appropriate for Generation Z employees require distinct approaches compared to those used with previous generations. As individuals who actively drive organizational and corporate development, Gen-Z employees currently within their most productive age range necessitate adaptive and effective leadership strategies. Objectives: This study aims to analyze the influence of effective leadership styles on the performance of Gen-Z employees at RSU Aulia, measured through the Key Performance Index (KPI) for the years 2023–2024. Method: A quantitative method with an associative approach was employed, using a cross-sectional design. A total of 150 Gen-Z employees (born between 1995 and 2010) participated in the study by completing a structured questionnaire. Result: The findings indicate that transformational and situational leadership styles yield the most positive impact on the KPI performance of Gen-Z employees. Conversely, autocratic and participative leadership styles were found to be relatively less effective within this demographic. Hypothesis testing revealed that the calculated F-value (2.683) exceeded the F-table value (0.874), indicating a statistically significant influence of leadership style (Variable X) on employee performance. The coefficient of determination (R²) was 0.085, suggesting that leadership styles accounted for 8.5% of the variance in employee performance, with the remaining 91.5% influenced by other factors. Conclution: The study concludes that transformational and situational leadership styles should be prioritized by RSU Aulia’s management to enhance Gen-Z employee performance. Furthermore, integrating coaching leadership approaches is recommended to support the fast-paced responsiveness and adaptability characteristic of Gen-Z employees.